Effect of Contrasting Cap Management Protocols on the Phenolic Composition, Redox Potential, and Sensory Properties of Pinot Noir and Petite Sirah Wines - Parnigoni, Dallas J. (2025)
Red wine cap management during alcoholic fermentation influences the extraction of phenolic compounds from grape solids and in turn affects oxygen consumption, oxidation–reduction potential (ORP), and must homogenization. Tailoring cap management protocols to influence these processes is essential for targeting wine style based on varietal and fruit composition. Herein, Pinot noir and Petite Sirah wines were produced with five cap management protocols, namely, pumpovers (POs), punchdowns (PDs), no cap management (NoCapMgmt), air mixing (AirMix), and nitrogen mixing (N2Mix). ORP of AirMix wines reached peaks of 340 mV and 240 mV in Pinot noir and Petite Sirah, respectively, while N2Mix wines were consistently below −50 mV during alcoholic fermentation. At pressing, treatments deemed oxidative, that is, AirMix, PO, showed the lowest concentrations of acetaldehyde, and treatments deemed reductive, that is, NoCapMgmt, N2Mix, the highest. Relative to PO wines at pressing, PD wines showed 22% increases in total phenolics in Pinot noir but insignificant differences in Petite Sirah. PD increased flavan-3-ol concentrations in both varietals. After 8 months of bottle aging, NoCapMgmt contained > 50% more esters than PD wines in both varietals. Ethyl n-decanoate and isoamyl acetate exhibited the highest odor activity values (OAVs) in all wines. Ethyl n-decanoate ranged from 121 (NoCapMgmt) to 69 (AirMix) in Pinot noir and 186 (NoCapMgmt) to 103 (PD) in Petite Sirah. Isoamyl acetate ranged from 52 (NoCapMgmt) to 20 (PD, AirMix, N2Mix) in Pinot noir and from 174 (NoCapMgmt) to 95 (AirMix) in Petite Sirah. In both varietals, AirMix wines showed decreased astringency and increased red fruit character, while N2Mix wines had higher color saturation and no reductive aromas despite consistently low ORP during alcoholic fermentation. Present results provide winemakers with tools to optimize fermentation kinetics and labor costs, selectively extract phenolic compounds, and produce wines of targeted style and sensory profiles in varietals with contrasting phenolic profiles.